Comparison of Glutues Maximus Activation to Flexion Bias Exercises Along with MET Technique in Subjects with Anterior Rotated Sacroiliac Joint Dysfunction—a Randomised Controlled Trial - Prem, PT, PHD, Venkatesan; Sanika, PT, Vaidya; Karvannan, PT, PHD, Harikesan (International Journal of Therapeutic Massage & Bodywork, 2020)
Background: Sacroiliac joint dysfunction (SIJD) is the primary source of lowback pain. Main muscles forming the force closure of sacroiliac joint are the biceps femoris and gluteus maximus which increase the stability through massive attachments via sacrotuberous ligament. However, there is a dearth of literature of the importance of activation of gluteus maximus in SIJD. Purpose: To study the effect of gluteus maximus activation on Oswestry Disability Index (ODI), visual analog scale (VAS), and pelvic tilt angle in subjects with anterior rotated sacrolilac joint dysfunction. Settings: The study was conducted in outpatient Physiotherapy Department, Manipal Hospital, Bangalore, India. Participants: Anterior rotated SIJD subjects were recruited in the study. They were divided into two groups (experimental and control groups) by block randomisation. Research Design: This is a randomised control trial. Controlled Treatment: Treatment order was determined by block randomisation. The subjects of both experimental and control group received Muscle Energy Technique (MET) technique on 1st session to correct the anterior rotated SIJD. The experimental group received gluteus maximus activation protocol, whereas the control group received flexion bias exercises. The groups received the treatment of 20 mins per session. There were two supervised sessions per week for four weeks. Main Outcome Measures: The primary outcome measure in the study is Oswestry Disability Index (ODI). The secondary outcome measures included visual analog scale (VAS) and Palpation Meter (PALM). Results: 48 subjects (26 females, 22 males) were randomised into experimental and control groups having anterior rotation SIJD, and average age in groups was 38.83 ± 11.4 years and 34.96 ± 9.5 years, respectively. The within-group analysis showed significant improvements in only ODI outcome of both the groups (p = .001). The between-group analysis in both groups did not show any statistical significant difference in ODI, VAS, or PALM. Conclusion: The flexion bias exercise and the gluteus maximus activation exercises used in this study were equally effective in improving physical function and reduction in pain, and maintaining the normal pelvic angle in subjects with anterior rotated SIJD.